Methods for calculating the parameters of drilling and blasting operations based on the primary determination of the zones of destruction of the rock mass - Оchilov Sh.А.; Маkhmudоv D.R.; Nizamova А.Т.; Norinov S.S.; Umirzokov А.А. (E3S Web of Conferences, 2024)
The article considers the dependences of determining the parameters of the destruction zones of the rock mass by explosive charges, proposed by V.N. Mosints, N.P. Gorbachev, M.F. Drukovanny, V.N. Tyupin, B.N. Kutuzov and A.P. Andrievsky and others. The above dependences allow determining the location of the boreholes in the face, taking into account the physical and mechanical characteristics of the massif being destroyed, the features of the explosive used, the variety of mining, geological and mining technical conditions for driving mine workings, as well as performing the calculation of rational parameters under conditions of increased rock pressure.